Morphological responses to biofertilization and vermicompost leachates application in mesquite seedlings - Carranza-Treviño, Joselyne; Alanís-Rodríguez, Eduardo; Sigala-Rodríguez, José Ángel; Molina-Guerra, Víctor Manuel; Jiménez-Pérez, Javier; Yáñez-Díaz, María Inés (Ecosistemas y Recursos Agropecuarios, 2025)
The application of vermicompost and plant growth-promoting bacteria are increasingly used biofertilization methods to reduce the use of synthetic fertilizers. However, their implementation in tree nursery species cultivation and their implications for producing tree seedlings for reforestation have been scarcely studied. In this study, fertilization with vermicompost leachates and inoculation with Azospirillum brasilense were assessed in mesquite seedlings (Prosopis laevigata) under nursery conditions. A factorial experiment was conducted with three vermicompost doses: 1) 0 (control), 2) 60 y 3) 120 mL L-1 and two inoculation levels: 1) with inoculation and 2) without inoculation. Plant height and diameter were monitored during the vegetative growth, and the biomass yield at the end of cultivation. Results showed a positive effect of fertilization with vermicompost on plant growth, but only at low doses. On the other hand, contrary to expectations, the inoculation with A. brasilense did not enhance the plant growth. Indeed, combined with high vermicompost fertilization, the inoculation inhibited plant growth. With these results, we confirm that it is possible to design biofertilization schemes to grow nursery tree seedlings, but the results also highlight the limitations that need to be considered for biofertilization implementation in practice.
Keywords: Azospirillum brasilense; Prosopis laevigata; vegetative growth; vermicompost